Revisiting Attribution Theory: Toward a Critical Feminist Approach for Understanding Attributions of Blame. Issue 2 (8th May 2021) - DelGreco, Maria; Denes, Amanda; Davis, Shardé; Webber, Katrina T
Abstract: Heeding the necessary call for interpersonal communication research to be theorized and conducted from a more critical perspective, we employ feminist standpoint theory as a critical tool for reading attribution theory. Specifically, we examine social positionality as an essential aspect of the attribution process and identify how oppressive power structures (macro-level) and a critical consciousness of one's social positionality (micro-level) impact interpersonal interactions (meso-level). Key components of our approach are visualized and applied to the context of sexual violence, and suggestions for additional interpersonal contexts to consider and ways to further the discussion are addressed. Overall, we maintain that taking a non-neutral, critical feminist approach to attribution theory enables us to consider how perspectives of marginalized groups are valuable sources of knowledge, interrogate how social positionality for those in power may impact attributions of blame, and recognize how groups in the margins have the agency to enact social change.